Using body-worn camera footage to remember use-of-force incidents - Bennell, Craig (The impact of technology on the criminal justice system, 2024)
Following their involvement in a use-of-force incident, police officers must usually complete an after-action report. These reports are used to help determine what occurred during the incident and whether the officer's use of force was reasonable and necessary. It is essential that these reports represent the officer's independent account of what transpired. Given that memory errors are likely to occur when officers attempt to recall these high-stress and dynamic events, a case has been made to use body-worn camera footage from recorded use-of-force incidents to facilitate officer recall. The current chapter highlights the implications of adopting such a practice. While research has shown that viewing video footage of experienced events can enhance one's memory for those events, viewing such footage can also contaminate memory, thus distorting officer recall. After reviewing this research, we make recommendations for how statements should be collected from police officers following their involvement in recorded use-of-force incidents to ensure that original, in-the-moment perceptions and memories are preserved.